Implementation of Santri Morals in Learning the Book of Washoya Aba' Lil Abna' in Dormitory F of the Matholi'ul Anwar Simo Sungelebak Islamic Boarding School - Muh Yazid; Imam Tholkha; Iqlimah Iqlimah; Aini Hidayati (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Indonesia's education world is currently trapped in preparing for instant human improvisation. At this time, parents generally force their children to be able to master the field of study in a relatively short time. Meanwhile, morality is a symbol of the quality of a servant. Therefore, morals determine the existence of a Muslim. Morals have an essential role in creating respectable humans in the eyes of humans and Allah, distinguishing them from other creatures. All of these are combined with the works of Sheikh Muhammad Syakir as a mirror for students who seek knowledge. The goal is none other than to be self-aware and to be able to control oneself adequately and appropriately. This research is a type of qualitative research. The data sources in this research consist of two parts, namely, primary data sources and secondary data sources. They are collecting data using interviews, observation, and documentation methods, documenting various descriptions related to the implementation of students by the teachings contained in the Washoya abaa 'lil abna' book and literature studies, including Studying materials associated with the object of research. Data analysis in this study was to take existing samples related to learning, human resources, place, and activity complexity after learning. The results of this study are: First, get to know more closely the students' morals applied in everyday life. Second, knowing the extent to which a santri can behave by his knowledge in everyday life because the biggest goal is to produce Sturdy Humans when they return to their respective homes, of course, by applying and being guided by the knowledge obtained at the boarding school, especially regarding Noble Morals because the Prophet was sent to perfect noble morals.